Identification and understanding of pre-term birth at kintampo municipal hospital: A qualitative cross-sectional study - pargah, l.k.; Udofia, Emilia (African Journal of Reproductive Health, ., 2011)
Up to 42% of nearly 10 million under five deaths occur in neonates with prematurity being a principal cause. This paper presents the outcome of a cross sectional qualitative study conducted among 14 hospital staff engaged in infant care in Kintampo, Ghana. Confidential interviews were used to evaluate their knowledge and practice of preterm care. Critical steps in caring for normal and preterm infants were ranked as adequate, satisfactory or inadequate if 75% or more, 50% to 74%, or less than 50% of the health workers completed them respectively. For term infants, adequate care was provided in terms of cleaning and wrapping, weighing, and initiating early feeds. Knowledge and practice were inadequate in relation to preterm care. Educational interventions emphasizing preterm care are recommended as an essential package for rural health workers. A newborn assessment tool was designed to address the gap in data collection identified during the study.
Keywords: adult; article; attitude to health; child care; cross-sectional study; female; Ghana; health care quality; hospital personnel; human; male; middle aged; morphometrics; newborn; organization and management; physical examination; prematurity; psychological aspect; public hospital; qualitative research